Beiträge zur Kenntnis alter naturwissenschaftlicher Werke. Beitrag 11. - Rautenberg, L. E. (Contributions to Entomology = Beiträge zur Entomologie, 1957)
Of the utmost rarity are the essays dealing with the insect fauna of a distinct territory published always in a small edition during the eighteenth and nineteenth century. One of these works is the „Beschreibung und Abbildung Schlesischer Insecten. Schmetterlinge", which came out in parts anonymously between 1819 and 1832 in Breslau. Only 4 incomplete copies of this work are hitherto known. One of them in the British Museum (N. H.) London contains the full number of 48 coloured lith. tables and is complete except the text of one table. Hagen already supposed the Kreissekretär Carl Friedrich Wilhelm Richter, an excellent expert of Silesian Lepidoptera, to be the author. Richter has published i. a. in Germar’s „Magazin der Entomologie" (1. Jahrgang, 1. Heft, pp. 72-113, 1813) an essay „Kritisches Verzeichniß der bisher bekannt gewordenen Schlesischen Schmetterlinge". With the aid of this work it was now possible to establish that Richter was the author of the „Beschreibung und Abbildung Schlesischer Insecten. Schmetterlinge".